Taxonomic study on the genus Fissicepheus (Acari: Oribatida: Otocepheidae) from China - Zheng, Li-Hao; Chen, Jun (Zootaxa, 2018)
Four new species of the genus Fissicepheus Balogh & Mahunka, 1967 from China are described on the basis of adults: Fissicepheus (Fissicepheus) aokii sp. nov., types from Shanxi Province, F. (F.) combicondylus sp. nov., from Guangdong Province, F. (F.) confragosus sp. nov., from Sichuan Province, and F. wangae sp. nov. from Beijing City. A revised generic diagnosis and a key to the 26 known species worldwide of Fissicepheus are provided. Compared with the diagnosis of the subgenus F. (Psammocepheus) Aoki, 1970, F. (P.) haradai Choi, 1986 is moved to the nominotypical subgenus: F. (F.) haradai Choi, 1986.